Management of chronic Achilles tendon ruptures—A review. (August 2016) - Malagelada, Francesc; Clark, Callum; Dega, Raman
Highlights: A fifth of Achilles tendon ruptures are undiagnosed on the first medical consultation. Those ruptures that are undiagnosed or mistreated will become chronic and will cause considerable functional morbidity. The management of chronic ruptures becomes a challenge to the treating doctor and a number of factors need to be taken into consideration, including patient's habitual level of activity and impairment caused, medical comorbidities, and condition of the soft tissues around the Achilles. Low-demand or high surgical-risk patients can be managed non-operatively with use of ankle-foot orthoses (AFO), although patient satisfaction is suboptimal. Multiple surgical techniques have been developed with good results being reported. Those can be broadly divided into repair, reconstruction or augmentation procedures. The lack of high-level clinical evidence precludes the support of one surgical technique over another. Abstract: Achilles tendon ruptures are increasingly common yet up to a fifth of them are undiagnosed after medical consultation. Those undiagnosed will become chronic ruptures causing considerable functional morbidity and represent a challenge to the treating doctor. The purpose of this article is to discuss the presentation and management of chronic Achilles tendon ruptures. Due to the paucity of data, evidence-based recommendations are unavailable. A number of different surgical techniques are presented and a working algorithm is described to aid in the treatment of these lesions.